Comparison of sealing ability of ProRoot mineral trioxide aggregate, biodentine, and ortho mineral trioxide aggregate for canal obturation by the fluid infiltration technique - Mousavi, Seyed Amir (Dent Res J (Isfahan), 2018)
BACKGROUND: Adequate seal of the root canal is necessary to prevent recontamination and ensure the long-term clinical success. The aim of this study was to evaluate the sealing ability of ProRoot mineral trioxide aggregate (MTA), Biodentine, and Ortho MTA as the root canal obturation materials using the fluid infiltration method. MATERIALS AND METHODS: In this invitro study a total of 66 extracted human mandibular premolars were randomly divided into five groups according to the material used for the root canal obturation. Group I - ProRoot MTA (20 samples), Group II - Biodentine (20 samples), Group III - Ortho MTA (20 samples), Group IV - negative group (3 samples), and Group V-positive group (3 samples). MTA, Biodentine, and Ortho MTA were applied using a cotton-tipped K-file #30 and hand plugger into the root canals of each group. In Group 4 (negative control), no filling material was used. In Group 5 (positive control), a single gutta-percha size #40 was inserted into the root canal without using a sealer. The teeth were mounted and exposed to the fluid infiltrarion system. Statistical analysis was performed using Kruskal–Wallis test the level of significance was set at α = 0.05. RESULTS: Mean values of microleakage in MTA ProRoot, Biodentine and Ortho MTA groups were 1.83 ± 0.62, 1.95 ± 1.27 and 1.72 ± 0.83 μL in 8 minutes. No statistically significant difference was observed between the sealing ability of ProRoot MTA, Biodentine, and Ortho MTA (P = 0.091). CONCLUSION: Within the limitations of this study, microleakage values were similar to MTA ProRoot, Biodentine, and Ortho MTA using the fluid infiltration technique.